Effect of Rotation Under the Influence of Gravity Due to Various Sources in a Generalized Thermoelastic Medium (Advances in Applied Mathematics and Mechanics, 2021)
The present problem is concerned with the study of deformation of arotating generalized thermoelastic medium under the influence of gravity.The components of displacement, force stress and temperature distributionare obtained in Laplace and Fourier domain by applying integral transforms.These components are then obtained in the physical domain by applying anumerical inversion method. Some particular cases are also discussed incontext of the problem. The results are also presented graphically toshow the effect of rotation and gravity in the medium.